Possible pharmacological therapeutic alternatives to haloperidol for Delirium: A thematic review - Prada-Betancourt, Isabella (2023)
Background: Delirium is a psychiatric syndrome with a high incidence in Colombia and around the world, making it a disease of significant relevance in emergency, hospitalization, and intensive care (ICU) settings. For many decades, haloperidol has been the first-line pharmacological treatment. However, this medication generates numerous adverse effects on the central nervous system (CNS), necessitating the search for alternative management options. Aim: This study aims to describe the different therapeutic alternatives to haloperidol for delirium, based on the current published literature. Materials and methods: A Narrative Review of the current literature was conducted, encompassing research articles and case reports from the Medline and Scielo databases. The study focused on patients over 18 years of age with delirium, who sought emergency room consultation, were hospitalized, or admitted to the intensive care unit (ICU), and were managed with haloperidol or different pharmacological alternatives. The objective was to identify and publicize potential agents with better evidence in delirium management and fewer adverse effects in the majority of the population. Results: The review compared various studies on delirium in different hospital areas managed with haloperidol and/or other pharmacological and non-pharmacological alternatives. However, it was noted that more in-depth investigations with larger population samples are required to determine the safety level of haloperidol and its pharmacological alternatives in the future. Nevertheless, the study provides valuable guidance for healthcare personnel in selecting the best pharmacological treatment, considering the variables unique to each patient. Conclusions: The current literature offers numerous randomized trials and observational studies that compare haloperidol with other antipsychotics, benzodiazepines, and other emerging drugs such as Suvorexant and Dexmedetomidine in delirium management, yielding promising results. The included meta-analyses in the review highlight similar conclusions: the majority of studies exhibit methodological biases, making it challenging to establish an optimal pharmacological scheme for delirium treatment. Therefore, it is crucial to address the underlying pathology of delirium and personalize the pharmacological and non-pharmacological treatment based on the individual needs and characteristics of each patient.